P35 Treatment with oleic acid and a pparα agonist increases fatty acid oxidation in beating human inducible pluripotent stem cell-derived cardiomyocytes. (21st March 2018) - Al-Siddiqi, H; Lopez, CA; Heather, LC; Carr, CA
Abstract : Aim: Human inducible pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) have an immature phenotype including a glycolytic metabolism. Here we aimed to mature the metabolic status of beating (hiPSC-CM) by targeting the PPAR-α pathway, which regulates the transcription of genes involved in fatty acid metabolism. We cultured hiPSC-CM with the fatty acid Oleic Acid (OA) with or without the PPAR-α agonist WY14643. Methods: hiPSCs cells were differentiated into beating hiPSC-CM by treatment with CHIR99021 followed by IWP4. Beating hiPSC-CM were treated with 400 uM OA with or without 120 uM WY14643 for 8 and 24 hours. Oxygen consumption was measured using a Clark-type oxygen electrode, glycolysis was measured by addition of 3H-glucose. Gene expression was measured using qPCR. Results: A significant increase in oxygen consumption and reserve respiratory capacity when respiring on fatty acid was?observed in beating iPSC-CM after culture with OA ±WY14643 for 24 hours compared with untreated and OA-treated hiPSC-CM. OA ±WY14643 caused a significant increase in expression of carnitine palmitoyltransferase 1B, medium chain acyl-CoA dehydrogenase and pyruvate dehydrogenase kinase after 8 hours whilst expression of glucose transporters and phosphofructokinase decreased. Addition of OA, but not OA ±WY14643, increased the rate of O2 respiration on pyruvate and malate but not the reserve respiratory capacity. There was no change in the rate of glycoysis after treatment with OA ±WY14643 for 24 hours. Conclusion: Treatment with OA and WY14643 for 24 hours increased fatty acid utilisation in beating hiPSC-derived cardiomyoyctes. Funded by the BHF and the Qatar Foundation.